PENGARUH MANAJEMEN BERBASIS NILAI TERHADAP KEPUTUSAN DIVESTASI DENGAN RISIKO TERKAIT KEPENTINGAN MANAJEMEN SEBAGAI VARIABEL MODERASI - Pramesti Meilana Rahayu; Grace Tianna Solovida (Universitas YPPI Rembang, 2023)
This study aims to analyze the influence of value-based management on divestment decisions with risks related to management interests as a moderating variable. This study uses the variable MBN Implementation Level as an independent variable, Risk Related to Management Interests as a moderating variable and Divestment Decision as the dependent variable. Sampling used a purposive sampling method from non-financial companies listed on the IDX and obtained a sample of 35 financial report data. Data were analyzed using the Statistical Program for Social Science (SPSS). The results of this study indicate that the level of MBN implementation can increase divestment decisions and risks related to management's interests strengthen the level of MBN implementation of divesment decisions.